2022
DOI: 10.1038/s41598-022-16322-z
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potential characterization and clustering using unsupervised algorithms of lactic acid bacteria from saltwater fish samples

Abstract: This research aimed to isolate lactic acid bacteria from the bowel of saltwater fish to assess their potential probiotic properties. Nineteen isolates of LAB including Lactiplantibacillus plantarum, Lactiplantibacillus pentosus, Lactobacillus acidophilus, Levilactobacillus brevis, Pediococcus pentosaceus, and Pediococcus acidilactici were recognized using molecular tools. All the isolates survived in the simulated conditions of the GI tract. Auto-aggregation ranged from 01.3 ± 0.5 to 82.6 ± 1.4% and hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(56 reference statements)
2
5
0
1
Order By: Relevance
“…In addition, it was shown that strains C3 and C18 had the highest hydrophobic properties, with rates of 65.30 ± 2.08 and 62.10 ± 1.33% with xylene and toluene, respectively. These results confirm the results of several previous works reported by Mazlumi et al 26 , Kiani et al 23 and Nami et al 27 .…”
Section: Resultssupporting
confidence: 93%
“…In addition, it was shown that strains C3 and C18 had the highest hydrophobic properties, with rates of 65.30 ± 2.08 and 62.10 ± 1.33% with xylene and toluene, respectively. These results confirm the results of several previous works reported by Mazlumi et al 26 , Kiani et al 23 and Nami et al 27 .…”
Section: Resultssupporting
confidence: 93%
“…Probiotics must adhere to the intestinal mucosa and not be easily removed from the gut by smoky bowel movements in order to colonize in the gut. Our findings are consistent with previous research, which found that only a few Lactobacillus strains, such as Y8 and C14, could adhere well to Caco-2 cells [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, constitutive or stressinduced bacterial aggregation has been shown to play an important role in bacteria-host interactions [88][89]. The candidates for targeted probiotics with lactic acid origin, including Lactiplantibacillus plantarum, Lactiplantibacillus pentosus, Lactobacillus acidophilus, Levilactobacillus brevis, Pediococcus pentosaceus, and Pedio-coccus acidilactici were also isolated and characterized by Mazlumi and coauthors [90]. Auto-aggregations of these bacteria was in the range from 01.3 ± 0.5 to 82.6 ± 1.4% [90].…”
Section: Discussionmentioning
confidence: 99%